The Place of Quantitative Methods in Life Cycle Costing (LCC) Applied in Travel Agencies - Biernacki, Michał (Miejsce metod ilościowych w rachunku kosztów cyklu życia wdrożonego w biurach podróży, 2011)
The strategic planning in travel agencies is based on the assumptions of Life Cycle Costing, which makes use of sales volume forecasts (forecasting both sales revenue and costas). The paper aims at discussing the place of the individual forecasting methods in the Life Cycle Costing (LCC) applied in travel agencies. There are presented some of the existing methods and models which are the most popular in practice, especially in travel agencies. There is showed a way and possibility of choosing a right method for this kind of companies.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 177, s. 9-18
Keywords: Life Cycle Costing; tourism service; forecasting; accounting; cost accounting